Pengaruh Kompetensi Sumber Daya Manusia terhadap Kinerja Operasional Biro Perjalanan Wisata pada D’jambi Holiday Tour - Asmara, Faza Azka; Saptoto, Robertus (IAI Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of human resource competence on the operational performance of the D’Jambi Holiday Tour travel agency. Human resource competence in this context includes the knowledge, skills, and work attitudes possessed by employees in carrying out operational tasks. A quantitative approach was used, with data collected through questionnaires distributed to both employees and management. The results show that human resource competence has a significant and positive impact on improving efficiency, service accuracy, and customer satisfaction. These findings indicate that continuous development of employee competence is crucial to supporting the operational success of travel agencies, especially in an increasingly competitive tourism industry.